RESPON KRISIS KERATON KASUNANAN SURAKARTA DALAM MEDIA - RATNA WILANDARI (Universitas Muhammadiyah Surakarta, 2016)
Crisis should be handled properly because it can threat the image and reputation oforganizations if it is too late to be handled. The fulfillment needs the information in terms of responding crisis communication was very important to consider a lot of outstanding issues in the society at the time of crisis. Media was the fulfillment needs information that was important for the society. At the time of crisis organization or institution should understand that the news was published in the media containing specific massage. The reasearch method is content analysis that can be used to learn caracteristic features of message. The purpose of this study was determine whether there was differences election crisis communicationresponse by category SCCT Theory in local media reports Solopos and Joglosemar period from februari until march 2014. The result showed that there was not difference in the election crisis communication response by SCCT Theory. This is evidenced by the data that the categorization of crisis response in the media Solopos was same categorization of crisis response found in Joglosemar media. Categorization crisis response is largest at Solopos that was Attack the accuser with 22 responses (28,9%) of 76 crisis response that was found. Whereas Joglosemar with 12 responses ( 31,5%) of 38 crisis response that was found.Response attack the accuser showed that the organization does not wanted to be blamed on the crisis, it is based on perspektive of the media.